Correlating Feed Efficiency with Ruminal Bacterial, Fungal, and Archaeal Community Composition in Dairy Cows over Two Lactations - Andrew J. Scheftgen; Joseph H. Skarlupka; Kelsea A. Jewell; Garret Suen (Dairy)
Dairy cows rely on their complex rumen microbial community to convert host-indigestible feed into nutrients usable for host growth, maintenance, and milk production. Previous work by our group found that the rumen bacterial community is dynamic over the course of two lactations and that cows with high and low milk production efficiency (MPE) have different taxa associated with either phenotype. Here, we characterized the ruminal fungal and archaeal communities to determine if these microbial populations exhibit properties similar to that of the rumen bacteria with respect to MPE over time. Our results show a decrease in fungal diversity over the course of both lactation cycles with an increase during the transition period. The fungal community had only a few taxa associated with efficiency. For the ruminal archaea, we found no change in diversity across both lactation cycles and only taxa in the genus Methanospera were found to be more abundant in high-MPE cows. Given that our previous study used 454 pyrosequencing, we also sought to determine if a resequencing of these communities using Illumina-based technology would alter our previous findings. We found that resequencing showed no significant deviation from our original broad conclusions, with the exception of some minor taxonomic associations.